EFFECTIVENESS OF MICRO-FERTILIZERS FOR PRE-SOWING SOYBEAN SEED TREATMENT - Shovkova, O. V.; Korotych, Ye. V. (Scientific Progress & Innovations, 2021)
Under modern conditions of agrarian production development in Ukraine, soybean is important as a valuable grain legume crop. Every year, new soybean varieties are introduced in production and the necessity arises to improve the existing technology elements in cultivating the crop. Balanced use of macro- and micro-elements not only optimizes the general balance of plant nutrition, raises fertilizers’ efficacy, improves resistance to stress and biotic factors, but also considerably increases yield capacity and the quality of obtained products. The purpose of the study was to identify the impact of pre-sowing seed treatment with chelate micro-fertilizers on the productivity of early-maturing soybean varieties in the Left-Bank part of the Forest-Steppe of Ukraine. The task of the study envisaged: to determine the effect of various chelate-based micro-fertilizers on structure indicators of soya seed yields; find the peculiarities of micro-fertilizers’ impact on yield capacity of early-maturing soya variety group. During the period of studies, the following scientific methods were used: analysis, synthesis, field, and statistical. The research results testify that the use of micro-fertilizers in the technology of soybean cultivation by pre-sowing seed treatment positively affects the formation of yield structure components in the experimental plants. The height of bean attachment on the lower layer in different soya varieties of early-maturing group varied from 13.2 to 15.9 cm depending on micro-fertilizers’ application. The largest number of beans per plant and thousand-seed weight was formed on the plots after pre-sowing seed treatment with Active Corn Legumes – 15.9–16.7 pcs and 167.3–190.5 g, respectively. The application of VUXAL KoMo Active micro-fertilizer ensured the yield increase of 0.22–0.28 t/ha depending on variety composition. Nano-mineralis micro-fertilizer was more effective: the yield increase made 0.47–0.56 t/ha. The maximum soybean productivity was formed at using Active Corn Legumes fertilizer with chelated micro-elements for pre-sowing seed treatment in the following varieties: Millenium – 3.43 t/ha, Amadeus – 2.87 t/ha, Raiduha – 3.25 t/ha, and Holubka variety – 3.57 t/ha.